After a catastrophe, a little bit of sex is better than nothing: Genetic consequences of a major earthquake on asexual and sexual populations. (22nd April 2020) - Becheler, Ronan; Guillemin, Marie‐Laure; Stoeckel, Solenn; Mauger, Stéphane; Saunier, Alice; Brante, Antonio; Destombe, Christophe; Valero, Myriam
Abstract: Catastrophic events can have profound effects on the demography of a population and consequently on genetic diversity. The dynamics of postcatastrophic recovery and the role of sexual versus asexual reproduction in buffering the effects of massive perturbations remain poorly understood, in part because the opportunity to document genetic diversity before and after such events is rare. Six natural (purely sexual) and seven cultivated (mainly clonal due to farming practices) populations of the red alga Agarophyton chilense were surveyed along the Chilean coast before, in the days after and 2 years after the 8.8 magnitude earthquake in 2010. The genetic diversity of sexual populations appeared sensitive to this massive perturbation, notably through the loss of rare alleles immediately after the earthquake. By 2012, the levels of diversity returned to those observed before the catastrophe, probably due to migration. In contrast, enhanced rates of clonality in cultivated populations conferred a surprising ability to buffer the instantaneous loss of diversity. After the earthquake, farmers increased the already high rate of clonality to maintain the few surviving beds, but most of them collapsed rapidly. Contrasting fates between sexual and clonal populations suggest that betting on strict clonality to sustain production is risky, probably because this extreme strategy hampered adaptation to the brutal environmental perturbation induced by the catastrophe.